The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41467-020-18583-6
|View full text |Cite
|
Sign up to set email alerts
|

Photobase effect for just-in-time delivery in photocatalytic hydrogen generation

Abstract: Carbon dots (CDs) are a promising nanomaterial for photocatalytic applications. However, the mechanism of the photocatalytic processes remains the subject of a debate due to the complex internal structure of the CDs, comprising crystalline and molecular units embedded in an amorphous matrix, rendering the analysis of the charge and energy transfer pathways between the constituent parts very challenging. Here we propose that the photobasic effect, that is the abstraction of a proton from water upon excitation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…The rate of D 2 evolution can reach 33.95 mmol g −1 h −1 under the full spectrum (Fig. 6c ), indicating that the origin of H 2 is aqueous protons 82 . The presence of the H/D isotope effect decreases the photocatalytic HER 83 , but in principle, it does not harm our inferences about the source of H 2 in the reaction systems.…”
Section: Resultsmentioning
confidence: 90%
“…The rate of D 2 evolution can reach 33.95 mmol g −1 h −1 under the full spectrum (Fig. 6c ), indicating that the origin of H 2 is aqueous protons 82 . The presence of the H/D isotope effect decreases the photocatalytic HER 83 , but in principle, it does not harm our inferences about the source of H 2 in the reaction systems.…”
Section: Resultsmentioning
confidence: 90%
“…*­(pCNDs) abstract a proton from the solvent. Such a protonated species undergoes electron transfer with an electron donor and produces CND-bound hydrogen radicals . In line with the assumption that a proton transfer from the solvent occurs on the picosecond time scale, fsTAS of our CND materials at a different pH was performed (Figures S27–S32).…”
Section: Discussionmentioning
confidence: 99%
“…The photobasic effect could not be corroborated in any of the cases. Nevertheless, it should be noted that only subtle spectral changes are expected for a proton transfer to CND . It is hard to unambiguously determine if the proton transfer occurs before, after, or concomitant with the electron transfer (step 2).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, with the enriched photogenerated carriers, the surface acid sites on the catalyst may change dramatically. [8] However, this phenomenon and its correlation to catalytic performance are often overlooked. MacFarlane et al [9] indicated that the decoration of hydrogensulfate on the carbon quantum dots endows the catalyst with the photoinduced acidity, promoting the acid-catalyzed ring-opening reaction of epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, with the enriched photogenerated carriers, the surface acid sites on the catalyst may change dramatically [8] . However, this phenomenon and its correlation to catalytic performance are often overlooked.…”
Section: Introductionmentioning
confidence: 99%